Switchable triple-wavelength thulium-doped fibre laser based on a Mach–Zehnder interferometer and fibre ring filter. Issue 15 (22nd August 2017) - He, Wei; Li, Da; Zhu, Lianqing; Dong, Mingli; Luo, Fei
Abstract: A switchable triple-wavelength thulium-doped fibre laser based on an all-fibre Mach–Zehnder interferometer and fibre ring filter with a polarization-maintaining fibre is proposed and experimentally demonstrated. In the proposed fibre laser, a Mach–Zehnder interferometer comprising two 1 × 2 optical couplers is inserted into the optical cavity to produce the comb filter effect. The fibre ring filter comprises two optical couplers with a 3:7 splitting ratio and a 2-m-long polarization-maintaining fibre to improve lasing stability. Single-wavelength lasing can be tuned continuously from 1864.4 to 1884.5 nm, and five different modes of dual-wavelength and switchable triple-wavelength lasers can be realized by changing the polarization state. The signal-to-noise ratios of all lasers are more than 33 dB. The maximum power fluctuations and wavelength variations are less than 1.5 dB and 0.3 nm at room temperature, respectively, and the 3 dB bandwidth is less than 0.2 nm. The results demonstrate that stable and switchable single- or dual-wavelength lasers can be generated using the designed fibre laser.